An overview on oil contaminated sand and its engineering applications - Abousnina, Rajab; Manalo, A.; Shiau, J.; Lokuge, W. (GEOMATE International Society, 2016)
Oil leakage is considered as one of the significant environmental issue worldwide, which affects the physical and chemical properties of the surrounding sand. A range of remediation methods for oil-contaminated sand was recommended but none are considered to be cost effective especially in developing countries. In order to find an alternative and cost-effective remediation method, the use of oil contaminated sand in engineering and construction has been considered. This paper reviews the main sources of oil contamination, the existing remediation methods and critically analysed several factors that affecting the properties of oil contaminated sand. Emerging applications of oil contaminated sand in engineering and construction are also presented.